Wild type Neurospora crassa strains preferred for use as standards - David D. Perkins (Fungal Genetics Reports, 2004)
The highly inbred Neurospora crassa strains 74-OR23-1VA (FGSC 2489) and 74-ORS-6a (FGSC 4200) are recommended for use as standard wild types.